Plan of a fort designed to be erected upon the harbour of St. Iohn's in Newfoundland mounting 112 cannon, and containing barracks, casemates, and store houses for 1000 men and their provisions of all spiecies [sic] for twelve months : Projected according to the orders of the Honble. Board of His Majesty's Ordnance dated the 3rd April 1765 / by Capt. Hugh Debbieg chief engineer of Newfoundland. - Debbieg, Hugh, 1731-1810.
Includes untitled section through the works.; Plan and section of fort proposed for the heights above the harbor as shown on Debbieg's plan of 1765 (Brun 52), with table of references identifying main features of the fort and its buildings.; Originally enclosed in: Debbieg to Gage, Sept. 28, 1765.